1997
DOI: 10.12968/bjon.1997.6.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing hospitalization: children with newly diagnosed diabetes

Abstract: Children's recognized vulnerability to the adverse effects of hospitalization has resulted in the firm belief that minimization or avoidance of hospitalization is in children's best interests. For children with newly diagnosed diabetes, minimal hospitalization may be achieved through the flexibility of the paediatric diabetes specialist nurse role, which crosses the boundary between hospital and community. This study was undertaken to evaluate the effectiveness of a paediatric diabetes specialist nurse in redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Three studies reported in four papers are included here by Swift and co-workers, 36 Lowes and Davis, 87 Lowes 88 and Couper and co-workers 89 ). Two were based in the UK 36,87,88 and one in Australia. 89 The studies will be referred to hereafter by the name of the first author.…”
Section: Home Care For Children With Insulin-dependent Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported in four papers are included here by Swift and co-workers, 36 Lowes and Davis, 87 Lowes 88 and Couper and co-workers 89 ). Two were based in the UK 36,87,88 and one in Australia. 89 The studies will be referred to hereafter by the name of the first author.…”
Section: Home Care For Children With Insulin-dependent Diabetesmentioning
confidence: 99%
“…Both Swift 36 and Lowes 87,88 report initial length of stay and readmissions ( Table 60). Both suggest that the introduction or promotion of home-based forms of care for children with IDDM leads to significant reductions in length of initial stay.…”
Section: Health Service Usementioning
confidence: 99%
“…Previous studies have considered the contribution of diabetes nurse specialists to diabetes care ( Wade & Moyer, 1989; Lowes & Davis, 1997) and the role of the diabetes nurse has been examined ( Kerrison, 1990; Moyer, 1994). Knowledge regarding diabetes nurse specialists’ perceptions when starting adult patients with insulin dependent diabetes mellitus on insulin seems to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of hospital stay is of interest for financial and economic reasons. Health care expenditure can be reduced by lowering the duration of hospital stay but also by an effective adjustment of metabolism (20–23). In Germany, children and adolescents with onset of type 1 diabetes are usually treated in an in‐patient setting.…”
Section: Discussionmentioning
confidence: 99%